Finite Element Analysis of Stress Distribution in Alkali-Peroxide Treated Epoxy Composites with Various Woven Cotton Structures - Owen M.M.; Wong L.S.; Achukwu E.O.; Shuib S.; Akil H.M. (Taylor and Francis Ltd., 2025)
The poor surface properties of woven epoxy-cotton composite structures have limited their use in industrial applications. Existing solutions using single treatment processes have been developed to address the challenges but have recorded appreciable degrees of success. This study has introduced a novel and synergistic alkali-peroxide treatment in addition to the use of five (5) variations of reinforcing woven structures (plain, matt, twill, herringbone, and satin) to develop the composites via the vacuum bagging molding process. This paper demonstrates the effectiveness of the dual treatment and different woven architectures in structure-related properties, particularly in the warp (machine) direction. The synergistic treatment showed a negative effect on the thermal stability of the resulting composites. The composite with the optimum weave structure in reinforcement capacity was validated using ANSYS FEA based on the numerical and experimental results, and the obtained results showed the possibility of simulating the tensile behavior of the composite structures. ? 2024 The Author(s). Published with license by Taylor & Francis Group, LLC.